Baptisan Roh Kudus dalam Teologi Pantekosta dan Implikasinya Bagi Hidup Orang Percaya - Perangin Angin, Yakub Hendrawan; Yeniretnowati, Tri Astuti (Ritornera - Jurnal Teologi Pentakosta Indonesia, 2021)
The question of what it means to be baptized with the Holy Spirit and how it happens, has created many great dividing lines and even endless debates from the past until now among Christians. Also the debate regarding the time and way of being baptized in the Holy Spirit also often becomes a polemic at the time of repentance or after? To answer this problem, this research was carried out using a qualitative method with a library approach, namely by collecting information from various textbooks and journals, then the researchers analyzed the concept of baptism and the concept of the baptism of the Holy Spirit as a conceptual framework that can provide a theological frame for how the baptism of the Holy Spirit is carried out. in Pentecostal Theology and its implications for believers. The conclusion of this study is how the implications of the baptism of the Holy Spirit which are agreed upon and experienced by people who believe in the Lord Jesus Christ increasingly give power and a very strong commitment to service for believers in their devotion to God.Pertanyaan tentang arti dibaptis dengan Roh Kudus dan bagaimana hal itu terjadi, sudah banyak membuat garis pemisah besar bahkan perdebatan yang tiada ujung dari dulu sampai saat ini di kalangan umat kristiani. Juga perdebatan terkait waktu dan cara seseorang dibaptis Roh Kudus juga sering kali menjadi polemik saat bertobat atau setelahnya?. Untuk menjawab permasalah ini maka dilakukan tinjauan pustaka, yaitu dengan cara menganalisis tentang konsep baptisan dan konsep baptisan Roh Kudus sebagai sebuah kerangka konsep yang dapat memberikan bingkai teologis bagaimana baptisan Roh Kudus dalam Teologi Pentakosta dan implikasinya bagi orang percaya. Implikasi dari baptisan Roh Kudus yang diamini dan dialami orang percaya semakin memberi kuasa dan komitmen pelayanan yang sangat kuat bagi orang percaya dalam pengabdiannya kepada Allah.